Pengembangan Perangkat Pembelajaran Aktif dengan Metode Practice Rehearsal Pairs pada Materi Suhu dan Kalor Untuk Meningkatkan Penguasaan Konsep Fisika - raodah, zahratur; ‘Ardhuha, Jannatin; Makhrus, Muh. (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2021)
Learning is a process of communication between teachers and students. The learning process will be successful if students achieve the expected competencies, because it can describe the ability of students to master a material. A teacher must be able to choose and use appropriate and effective learning methods. This research aims to develop active learning tools with practice rehearsal pairs methods that are suitable for use in learning and can improve students' mastery of physics concepts. This research is a research and development (R&D) with a 4D development model design consisting of 4 stages, namely: define; design; develop; and disseminate. The pandemic condition has made this research only at the develop stage. Based on validation by experts, the development of learning tools in this research is quite valid and reliable. The percentage of validity is 80.83% on the syllabus; 83.33% on the lesson plan implementation; and 79.17% on student worksheets. Meanwhile, the percentage of reliability is 89.40% on the syllabus; 89.70% on the lesson plan implementation; and 91.20% on student worksheets. Based on these results, the development of learning tools in this research is feasible to use with revisions, because it has quite valid criteria.